Telemedical monitoring and coaching improves survival and hospitalisation rates in heart failure. (3rd October 2022) - Knoll, K; Rosner, S; Trenkwalder, T; Lennerz, C; Dittrich, D; Kloss, C; Doerr, M; Schunkert, H; Reinhard, W
Abstract: Aims: To investigate the effectiveness of a combined telemonitoring and telecoaching programme for chronic heart failure patients at high risk for hospitalisation compared to usual care in a real life setting. The applied telehealth programme consisted of regular individualised telecoaching sessions as well as daily remote telemonitoring of heart failure signs and symptoms. Methods: Between January 2018 and September 2020, 6, 065 heart failure patients were enrolled in a combined telehealth programme and retrospectively compared to a propensity matched usual care group (n=6, 065). All participants were members of a statutory health insurance. Median follow-up was 442 days (IQR 309–681). Endpoints were all cause mortality, number and duration of hospitalisations. Results: After 1 year the combined telecoaching and telemonitoring programme significantly reduced all-cause mortality probability compared to usual care (11.0 vs. 5.8%, p<0.001). The corresponding number-needed to treat to prevent one death in one year was 19.3. In addition, the number of hospitalisations for heart failure (17.9 vs. 21.8 per 100 patient years, p<0.001) and all cause hospitalisations (129.0 vs. 133.2, p=0.015), as well as their duration (2.0 vs. 2.6 days per year p<0.001, and 12.0 vs. 13.4 days per year p>0.001, respectivel y) were significantly lower in the telehealth group than in the usual care group. Conclusion: In ambulatory heart failure patients at high risk for hospitalisation, a combined telemonitoring and telecoaching programme led to a reduction of heart failure hospitalisations and all-cause mortality compared to standard care. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Health Care Systems GmbH (HCSG), Pullach i. Isartal